Polemik Naiknya Biaya Perjalanan Haji di Indonesia Tahun 2023 di Tinjau dari Siyasah Maliyah - Siregar, Muhammad Rizki Aulia; Syam, Syafruddin (UNES Law Review, 2023)
The pilgrimage is mandatory for Muslims who are able to carry it out. In Indonesia, Hajj travel costs are managed by the Hajj Financial Management Agency. The cost of organizing the Hajj pilgrimage always experiences adjustments from time to time in line with changes in economic conditions in Indonesia and the world. The aim of this research is to determine the causes and factors of the increase in the cost of the Hajj pilgrimage which has caused polemics in society and is reviewed from the Maliyah siyasah. This can be seen from external factors, namely movements in world oil prices, the rupiah exchange rate which can influence the determination of Hajj Organizing Fees in Indonesia. This research uses a qualitative method with a research approach and analysis of facts in the field. The author found that the increase in the price of aircraft oil (avtur and avgas) and the exchange rate (rupiah to US dollar) can influence the determination of Hajj Organizing Fees. The role of the Hajj financial management body here is very central because all Hajj finances are managed by this institution. The benefits of Hajj financial funds must be felt by all prospective pilgrims who have registered themselves to carry out the Hajj pilgrimage.